Microenvironmental Variations After Blood-Brain Barrier Breakdown in Traumatic Brain Injury - Hu, Yue; Tao, Weiwei (Frontiers in Molecular Neuroscience, 2021)
Traumatic brain injury (TBI) is linked to several pathologies. The blood-brain barrier (BBB) breakdown is considered to be one of the initial changes. Further, the microenvironmental alteration following TBI-induced BBB breakdown can be multi-scaled, constant, and dramatic. The microenvironmental variations after disruption of BBB includes several pathological changes, such as cerebral blood flow (CBF) alteration, brain edema, cerebral metabolism imbalances, and accumulation of inflammatory molecules. The modulation of the microenvironment presents attractive targets for TBI recovery, such as reducing toxic substances, inhibiting inflammation, and promoting neurogenesis. Herein, we briefly review the pathological alterations of the microenvironmental changes following BBB breakdown and outline potential interventions for TBI recovery based on microenvironmental modulation.